2022
DOI: 10.3389/fimmu.2022.1008778
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analysis reveals the relationship between RCSD1 immune infiltration and clinical prognosis in human tumors

Abstract: BackgroundRCSD1 is a cytoskeletal regulator that has been confirmed to undergo genetic mutations in hematological tumors, but the mechanisms of RCSD1 in pan-cancer and its impact on patient prognosis have not been studied.MethodsUsing TCGA, GEPIA, UALCAN, Kaplan-Meier plotters, Linkedomics, String, cBioPortal, TISIDB, TCIA and TIMER database methods, we investigated the expression of RCSD1 in human tumors and its relationship to clinical prognosis, functional analysis of co-expression networks, mutation status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Our results revealed that PREX1 was positively correlated with KCTD12, HEG1, RASSF2, FMNL3 and RCSD1, with the most significant correlation with RCSD1. Previous research has demonstrated that RCSD1 is positively related to infiltrating macrophages in lung cancer 30 . FMNL3 play a critical role in the recruitment of TILs and inflammatory tumor microenvironment 31 .…”
Section: Discussionmentioning
confidence: 91%
“…Our results revealed that PREX1 was positively correlated with KCTD12, HEG1, RASSF2, FMNL3 and RCSD1, with the most significant correlation with RCSD1. Previous research has demonstrated that RCSD1 is positively related to infiltrating macrophages in lung cancer 30 . FMNL3 play a critical role in the recruitment of TILs and inflammatory tumor microenvironment 31 .…”
Section: Discussionmentioning
confidence: 91%
“…Several of our identified genes are related to the immune response in various cancer types, including PDAC. For example, both CD37 and RCSD1 are linked to recruitment of anti-tumour immune cells and improved prognoses [ 91 , 92 ]. ITK is implicated in immune checkpoint process [ 93 ], C1R is an immunosuppressive complement effectors protein [ 94 ] and IL7R regulates in lymphocyte development [ 95 ].…”
Section: Discussionmentioning
confidence: 99%